A Study Of Servqual And Customer Satisfaction Using Customer Satisfaction Index (Csi), Importance Performance Analysis (Ipa) And Improvement Factor (If) Method - Ginting, Yanti Mayasari; Chandra, Teddy; Oktariyanto, Oktariyanto; Endrawati, Endrawati (Economics and Digital Business Review, 2024)
This research aims to determine, calculate, test and analyze the level of customer satisfaction in Citra Harapan Motor Bukittinggi (measured by CSI, IPA and IF methods). This study uses service quality variables with 5 (five) dimensions, namely tangible, reliability, responsiveness, assurance and empathy). This study uses a sample of 116 respondents who are customers of Citra Harapan Motor Bukittinggi. Data were analyzed using Analysis of Variation (ANOVA) with SPSS 22. The results showed that the overall level of consumer satisfaction (based on CSI values) was 79.58%. This value is between 60% - 79.99% which indicates that the consumer satisfaction index was "Satisfied" criteria.